Microsatellite markers in candidate genes for wood properties and its application in functional diversity assessment in Eucalyptus globulus - Acuña, Cintia Vanesa (2012)
Background: Functional genetic markers have important implications for genetic analysis by providing direct estimation of functional diversity. Although high throughput sequencing techniques for functional diversity analysis are being developed nowadays, the use of already well established variable markers present in candidate genes is still an interesting alternative for mapping purposes and functional diversity studies. SSR markers are routinely used in most plant and animal breeding programs for many species including Eucalyptus. SSR markers derived from candidate genes (SSR-CG) can be used effectively in co-segregation studies and marker-assisted diversity management. Results: In the present study, eight new non reported SSRs were identified in seven candidate genes for wood properties in Eucalyptus globulus: cinnamoyl CoA reductase (CCR), homocysteine S-methyltransferase (HMT), shikimate kinase (SK), xyloglucan endotransglycosylase 2 (XTH2), cellulose synthase 3 (CesA3), glutathione S-transferase (GST) and the transcription factor LIM1. Microsatellites were located in promoters, introns and exons, being most of them CT dinucleotide repeats. Genetic diversity of these eight CG-derived SSR-markers was explored in 54 unrelated genotypes. Except for XTH2, high levels of polymorphism were detected: 93 alleles (mean of 13.1 sd 1.6 alleles per locus), a mean effective number of alleles (Ne) of 5.4 (sd 1.6), polymorphic information content values (PIC) from 0.617 to 0.855 and probability of Identity (PI) ranging from 0.030 to 0.151. Conclusions: This is the first report on the identification, characterization and diversity analysis of microsatellite markers located inside wood quality candidate genes (CG) from Eucalyptus globulus. This set of markers is then appropriate for characterizing genetic variation, with potential usefulness for quantitative trait loci (QTL) mapping in different eucalypts genetic pedigrees and other applications such as fingerprinting and marker assisted diversity management.